COVID-19 and Monetary Policy Responses - Purba, Martin Luter; Sihotang, Jusmer; Sitinjak, Ruth Betaria; Lumban Gaol, Vebry M; Nopeline, Nancy (Law and Economics, 2026)
The COVID-19 pandemic has profoundly impacted the world economy, especially Indonesia, causing substantial fluctuations in essential macroeconomic indices such as economic growth, inflation, and financial markets. In response, Bank Indonesia executed a series of monetary policy modifications, chiefly by augmenting the money supply to guarantee liquidity and stabilize the economy. The efficacy of monetary policy transmission during extraordinary crises is debatable due to structural changes and increased uncertainty. This study seeks to analyze the dynamic relationships between money supply, inflation, and economic growth in Indonesia from 2013 to 2024, specifically contrasting patterns before and during the pandemic. The study utilizes a quantitative methodology, specifically the Vector Autoregression (VAR) model and Granger causality tests, to ascertain the direction and magnitude of correlations among variables. The results aim to deliver empirical evidence about the effectiveness of monetary policy in alleviating economic disruptions during health emergencies, so providing significant policy recommendations for central banks encountering analogous issues in the future